DIELECTRIC RELAXATION STUDIES OF SOME AROMATIC HYDROCARBONS AND THEIR NAPHTHENE MIXTURES - Ahmad, S Shakil; Yaqub, Mohammed; Nasir, Khalil A (Biological Sciences - PJSIR, 2001)
The frequency dependence of complex dielectric constant £*, and the loss factor 'tan 8' for xylene isomers (para, meta and ortho-xylene), pure naphthene and 50% mixture of naphthene have been studied from I 00 KHz to 100 MHz. The dielectric relaxation process h as also been studied. The data has been analyzed in terms of Cole-Cole and Higasi type distribution. The results obtained for xylene isomers are in agreement with, Cole-Cole type of semicircle representation. Relaxation time 't' has been calculated from viscosity data obtained from Happlier apparatus, at four different temperatures. To study the effective relaxation mechanism of molecules in polar solute and solvent and their mixtures, along with the given values of heat of absorption of these liquids, Hartshorn and Ward apparatus has been used for the measurement of dielectric parameters . The results support our assumption that the dielectric absorption in xylene isomers is due to overall molecular rotation.